Metabolic syndrome predicts postoperative complications after gastrectomy in gastric cancer patients: Development of an individualized usable nomogram and rating model - Xiaodong Chen; Weiteng Zhang; Xiangwei Sun; Mingming Shi; Libin Xu; Yiqi Cai; Wenjing Chen; Chenchen Mao; Xian Shen (Cancer Medicine)
Abstract Background Metabolic syndrome (MetS), a public health problem, is reportedly related to an increased risk of postoperative complications after surgery. However, whether MetS have an effect on complications after gastric cancer (GC) surgery are unknown. This study aimed to investigate the effects of preoperative MetS on complications after gastrectomy. Methods Altogether, 718 gastric cancer patients who planned to receive radical gastrectomy between June 2014 and December 2016 were enrolled, demographic and clinicopathological characteristics were analyzed. Univariate and multivariate analyses were performed to identify potential risk factors for postoperative complications. A predictive model for postoperative complications was constructed in the form of a nomogram, and its clinical usefulness was assessed. Results Of the 628 patients ultimately included in the study (mean age 62.92 years, 450 men and 178 women), 84 were diagnosed with MetS preoperatively. Severe postoperative complications (Clavien‐Dindo grade ≥II) were significantly more common in patients with MetS (41.7% versus 23.7%, P < .001). Predictors of postoperative complications included MetS (odds ratio [OR] = 1.800, P = .023), age (OR = 1.418, P = .050), Charlson score (OR = 1.787, P = .004 for 1‐2 points) and anastomosis type (OR = 1.746, P = .007 for Billroth II reconstruction). The high‐risk rating had a high AUC (ROC I = 0.503, ROC Ib = 0.544, ROC IIa = 0.601, ROC IIb = 0.612, ROC IIc = 0.638, ROC III = 0.735), indicating that the risk‐rating model has good discriminative capacity and clinical usefulness. Conclusions MetS was an independent risk factor for complications after gastrectomy. The nomogram and rating model incorporating MetS, Billroth II anastomosis, age, and Charlson score was useful for individualized prediction of postoperative complications.